COLOR OF ART FASHION DIGITAL PRINTING DENGAN SUMBER IDE KARAKTER TRESILO - Ovalin Sitohang (Universitas Negeri makassar, 2023)
Color has influenced all kinds of aspects including: fashion design, graphic design, advertising, games and many other things. a color can be seen from the perception of each person differently. The purpose of this study is to create high chorma colors that originate from the Tresillo character, to find out the color results produced in digital printing techniques using Polyester fiber fabric, namely maxmara. High chroma can be obtained by means of digital printing for art fashion colors. It is this color that gives a lively and lively effect to art fashion, hue and chorma are important aspects of the color output. research methods using experiments with data collection using literature studies, exploration, and documentation.